Strategi dan Tantangan Industri Halal di Era 5.0 - Ayu Wulandari , Retno Ayu Wulandari (Fakultas Syariah dan Ekonomi Islam, 2023)
Indonesia has the largest Muslim papulation in the word. Indonesia has a great opportunity to the develop the halal industry in various aspects. The growth potential of the halal industry is increasing along with the increas in the world’s Muslim population. To achieve maximum development of the halal industy, a strategy is needed to regulate the course of production. The strategy includes planning, implementing, and supervising the implementation of the industry. In the midst of the productions of the halal industry, of course there are a number of challengers that become obstacles. Among the challengers of the halal industry in the general, lack of focus on developing halal products, there are competitors from non-Muslim countries developing the halal industry, and a lack of understanding UMKM about the importance of halal certification